Kindergarten Teachers as Educators, Mentors, and Facilitators for Children with ADHD: Guru Taman Kanak-Kanak sebagai Pendidik, Pembimbing, dan Fasilitator bagi Anak-Anak dengan ADHD - Ramadani, Lia; Mahabbati, Aini (Indonesian Journal of Innovation Studies, 2025)
Background (General): Early childhood is a critical developmental stage where socio-emotional growth determines later academic and social success. Globally, children with Attention Deficit Hyperactivity Disorder (ADHD) face challenges in attention, impulse control, and social adjustment. Background (Specific): In Indonesia, ADHD cases among preschool children are increasing, yet interventions remain dominated by medical approaches, while the role of teachers in socio-emotional support has been underexplored. Knowledge Gap: Prior studies mainly emphasize clinical symptoms or general pedagogy, leaving limited understanding of how kindergarten teachers implement socio-emotional interventions within inclusive classrooms. Aim: This study investigates the role of kindergarten teachers in supporting children with ADHD symptoms, focusing on strategies for socio-emotional development in TK Negeri 2 Kaubun. Results: Using a qualitative case study, findings show teachers acted as educators, mentors, and facilitators, employing multisensory learning, positive reinforcement, quiet spaces, and parent collaboration. These interventions improved children’s emotional regulation, focus, and social participation, despite persistent challenges such as impulsivity and limited teacher time. Novelty: The study highlights adaptive and context-specific teacher practices in Indonesia, offering insights beyond clinical or Western-centered approaches. Implications: Results inform teacher training, inclusive education policies, and collaborative school–parent strategies, reinforcing the need for systemic support in early childhood inclusive education.Highlight : Teachers play a central role in guiding children with ADHD symptoms. Consistent interventions enhance emotional regulation and social interaction. Collaboration and inclusive policies strengthen learning support. Keywords : Teacher's Role, Social-Emotional Intervention, Early Childhood, Attention Difficulties, Hyperactive Behavior